Nuclear exclusion of transcription factors associated with apoptosis in developing nervous tissue - Linden,R. (1999)
Programmed cell death in the form of apoptosis involves a network of metabolic events and may be triggered by a variety of stimuli in distinct cells. The nervous system contains several neuron and glial cell types, and developmental events are strongly dependent on selective cell interactions. Retinal explants have been used as a model to investigate apoptosis in nervous tissue. This preparation maintains the structural complexity and cell interactions similar to the retina in situ, and contains cells in all stages of development. We review the finding of nuclear exclusion of several transcription factors during apoptosis in retinal cells. The data reviewed in this paper suggest a link between apoptosis and a failure in the nucleo-cytoplasmic partition of transcription factors. It is argued that the nuclear exclusion of transcription factors may be an integral component of apoptosis both in the nervous system and in other types of cells and tissues.